An Integrated Modeling Approach Combining Multifractal Urban Planning with a Space Syntax Perspective - Claudia Yamu; Akkelies van Nes (Urban Science, 2017)
The United Nations Paris agreement of 2015 highlighted the need for urban planning to prevent and contain urban sprawl so as to reduce trip lengths through an efficient distribution of agglomerations and a well-balanced urban pattern distribution, all while considering travel behavior and accessibility to green areas, services, and facilities on different temporal scales. For the Vienna-Bratislava metropolitan region, our integrated modeling approach uses a combination of multifractal spatial modeling along with a space syntax perspective. Multifractal strategies are intrinsically multiscalar and adhere to five planning principles: hierarchical (polycentric) urban development to manage urban sprawl; sustainable transit-oriented development; locally well-balanced urban pattern and functions distribution to enhance vital urban systems, local centers, and neighborhoods; penetration of green areas into built-up areas; and the preservation of large interconnected networks of green areas to conserve biodiversity. Adding space syntax modeling to a multifractal strategy integrates how space relates to functional patterns based on centrality, thus applying a socio-spatial perspective. In this paper, we used the following workflow for an integrated modeling approach: (1) Space syntax to identify the urban systems’ hierarchy and so determine a spatial strategy regionally; (2) Fractalopolis to create a multifractal development plan for potential urbanization; and (3) Space syntax to design a strategic urban master plan for locating new housing and facilities vis-à-vis socioeconomic factors.